FAKTOR PENYEBAB WISATAWAN DOMESTIK MELAKUKAN MEETING DAN CONVENTION DI HOTEL LIDO KABUPATEN BOGOR - Sylmi Kamila, - (2009)
Lido Hotel Resort was build in 1935 by a Dutchman named or called Antonius Johanes Ludoficus Maria Zwijsen, that used as a place to rest and recreation that designed with Dutch style. This Hotel gave Meeting and Convention facilities. Conference and banquet facilities at Hotel Lido fully equipped and meeting room with peacefull surroundings around location makes a perfect location for used to seminar, meeting and conference. Business meeting and trading that include before and after convention tour become more populer. Meeting planner will offer a full package, including all the element of meeting or conventiom as activities. Mostly that come for meeting and convention at Hotel Lido is a domestic tourist. For that the researcher is willing to know what factor that makes domestic tourist do meeting and convention at Lido Lakes Resort and Conference Bogor. Research method that used is " Metode Deskriptif Pendekatan Survey", is a method in research status human group, a certain object, a certain condition, a certain thinking, or a certain moment at this time. Result that researcher found or get from the guest reason and committee choose to do meeting anf conference at Hotel Lido as : • Friendly service from official employeee of the Hotel. • Fast or quick services. • Pleasant or comfort and relax. • Clean building and good treated building. • Meeting room or conference prepared well and approriated. • All equipment that need for meeting and convention is filfilled. • Equipped by facilities besides meeting and convention. Hopefully factors and chance that become benefits can help Hotel Lido Lakes Resort and Conference could become one of developing Hotel with meeting and convention.